META-TECHNOLOGIES OF BUSINESS AND PROFESSIONAL CONSULTING IN EDUCATIONAL ORGANIZATIONS - Kassymova, G.K.; Krasnoshchechenko, I.P.; Menshikov, P.V.; Kosov, A.V.; Khudyakova, T.L.; Klepach, Ju.V.; Stepanova, O.P.; Podol’skaya, I.A.; Arpentieva, M.R. (Scientific Journal of Pedagogy and Economics, 2020)
The article is devoted to the analysis of the main principles of business and professional consulting as a practice of interpersonal relations and the being of its subjects. The main problems of clients connected with violations of their intrapersonal and interpersonal relations, as well as relations to their own life (being) in general, subjects of business consulting as participants in business processes and life, in general, are considered. The purpose of the study is to analyze the basic principles or meta-technologies of business and professional consulting in educational organizations. The article summarizes the basic concepts and concepts of business and professional consulting, reflecting its meaning as helping the socio-psychological practice of developing people and educational organizations. Relying on the tetrad of principles of psychological counselling, isolated in the school of C.R. Rogers, as well as the leading principles of organizational counselling in educational organizations, the authors consider their manifestations and features in the main aspects and dimensions of advisory interaction. Traditionally, such dimensions are distinguished: power/management system, competence/experience system, love/system of relations. Each of these dimensions is associated with one or another intention of consultative relations in educational organizations: transformational, dialogical, and relational. Within each of these intentions, the basic principles of business and professional consulting in educational organizations are manifested as meta-technologies or meta-technology groups. In addition, the authors consider the principles of business and professional consulting in educational organizations in relation to the life of the consultant and the client as a whole, as "meta-technologies of life".